The Influence of Concomitant Hammertoe Correction on Postoperative Outcomes in Patients Undergoing Hallux Valgus Correction. Issue 2 (April 2022) - Rajan, Lavan; Fuller, Robert; Zhu, Jiaqi; An, Tonya W.; Ellis, Scott J.
Category: Bunion; Lesser Toes Introduction/Purpose: Patients with hallux valgus often develop secondary hammertoe deformities of the lesser toes. Chronic lateral deviation of the hallux leads to proximal interphalangeal joint flexion contracture, metatarsophalangeal joint subluxation and ultimately a cross-toe deformity. Operative management of bunions with hammertoe is more extensive since both the primary bunion deformity and the secondary defect have to be corrected simultaneously; however, it is unclear whether simultaneous bunion and hammertoe correction affects patient outcomes. The objective of this study was to compare postoperative patient reported outcomes using the patient-reported outcome measure information system (PROMIS) scores and radiographic outcomes between patients who underwent isolated bunion deformity correction and patients who underwent operative repair of hallux valgus with concomitant hammertoe correction. Methods: This retrospective cohort study included patients over the age of 18 who were treated operatively by 1 of 7 fellowship-trained foot and ankle surgeons for hallux valgus. Those with clinically symptomatic hammertoes were also corrected at the surgeon's discretion. All patients had minimum 1-year postoperative PROMIS scores and minimum 3-month postoperative radiographs. Preoperative, final postoperative and change in PROMIS scores from 6 domains (physical function, pain interference, pain intensity, global physical and mental health, and depression) were compared between the isolated bunion and bunion with hammertoe correction groups. Radiographic measurements compared between cohorts included hallux valgus angle (HVA), intermetatarsal angle (IMA), distal metatarsal-articular angle (DMAA), and Meary's angle. Radiographic parameters were measured on anteroposterior (AP) and lateral weightbearing radiographs. Statistical analysis utilized targeted minimum-loss estimation (TMLE) to control for confounders (age, gender, BMI). Results: A total of 221 patients (134 with isolated bunion correction, 87 with concomitant hammertoe correction) with an average of 19.2 months follow-up were included in this study. Demographically, patients in the concomitant hammertoe cohort were older than the isolated bunion group (58.5 vs 53.1, p<0.01) and had a higher BMI (24.8 vs 58.5, p<0.05). Both cohorts demonstrated improvement in all PROMIS domains except for global mental health and depression. The isolated bunion cohort had significantly better improvements in pain interference and pain intensity when compared to the concomitant hammertoe group (p<0.01, p<0.05 respectively) (Table 1). The isolated bunion cohort had lower postoperative pain interference scores (p<.01). Radiographically, the concomitant hammertoe group had a higher preoperative HVA than the isolated bunion group (30 vs 27.6, p<.05). There were no statistically significant differences between the two cohorts in postoperative radiographic parameters, in addition to the probability of achieving normal postoperative radiographic measures. Conclusion: Patients undergoing simultaneous bunion and hammertoe correction experienced worse postoperative outcomes measured by PROMIS pain interference, had significantly less improvement in PROMIS pain interference and pain intensity scores, and had more severe preoperative radiographic deformity when compared to those who underwent isolated bunion correction. The relationship between hallux valgus and hammertoe development should be considered when counseling patients for surgery. Patients with hallux valgus who show early signs of hammertoe formation such as second toe elevation or pain under the second metatarsal head may benefit from earlier bunion correction before the hammertoe progresses to the point of needing surgical management.